2002
DOI: 10.1093/humupd/8.4.385
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the prevalence of Chlamydia trachomatis among European women

Abstract: The study aim was to establish by systematic review the prevalence of asymptomatic Chlamydia trachomatis infection of the lower female genital tract in Europe and also to assess the extent and effect of screening. The search process was wide ranging, using the electronic databases Medline, Embase and Aidsline and the Internet using the search engines Netscape and Euro-ferret. Studies published in any language during 1980-2000 were included if they unambiguously reported prevalence of C. trachomatis infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 69 publications
12
61
0
5
Order By: Relevance
“…These considerations are confi rmed by the fact that in the latter group of women we observed a signifi cant difference in the positivity for antibodies of classes IgA and IgG (7.3 % vs 14.5 %) and direct detection of the agent by the PCR method showed only 1.5 % positivity. Results obtained in our study agree with those obtained in other countries which indicated that C. trachomatis infection occurred more frequently in young, sexually active women, particularly in adolescents (9,10,11,12).…”
Section: Discussionsupporting
confidence: 92%
“…These considerations are confi rmed by the fact that in the latter group of women we observed a signifi cant difference in the positivity for antibodies of classes IgA and IgG (7.3 % vs 14.5 %) and direct detection of the agent by the PCR method showed only 1.5 % positivity. Results obtained in our study agree with those obtained in other countries which indicated that C. trachomatis infection occurred more frequently in young, sexually active women, particularly in adolescents (9,10,11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Esto coincide con estudios previos en los que se han reportado prevalencias elevadas para diferentes poblaciones; así, en Colombia en población general es 6% 4,5 . Una revisión sistemática de estudios publicados entre 1980 y 2000 en mujeres asintomáticas de Europa reportó una magnitud de la infección en un rango entre 1,7% y 17%, dependiente de la población y el país de estudio 10 .…”
Section: Discussionunclassified
“…En este sentido, se puede resaltar el estudio del grupo de Newman en 2012 que, con base en estudios seleccionados mediante una revisión sistemática de reportes globales de ITS, encontró una prevalencia de 4,2% (IC 95 = 3,7-4,7) en mujeres entre 15 y 49 años 9 . Una revisión sistemática de estudios publicados entre 1980 y 2000 en mujeres asintomáticas de Europa, reportó prevalencias en un rango entre 1,7% y 17%, dependiente de la población y el país de estudio 10 .…”
Section: As Infecciones De Transmisión Sexual (Its)unclassified
“…1,[21][22][23][24] On the other hand, in developed countries, the prevalence levels range from less than 2% to 8-10% in general population and from less than 5% to 20% among female adolescents. 1,25 In Argentina, many prevalence studies of CT infection have been conducted among women, but these studies have two important shortcomings: (I) most of them used non-standardized populations, different analytical methods to detect CT or only considered symptomatic cases; and (II) there is scarce epidemiological information about populations from northern Argentina, the region with the highest reported clinical diagnosis of STBI of the country. The available data show that prevalence ranges from 1.8% to 13% in the general population and from 20% to 47% in women with gynecological alterations.…”
Section: Discussionmentioning
confidence: 99%